Ocular effects caused by viral infections and corresponding vaccines: An overview of varicella zoster virus, measles virus, influenza viruses, hepatitis B virus, and SARS-CoV-2 - Scalabrin, Simona; Becco, Alice; Vitale, Alessio; Nuzzi, Raffaele (Frontiers in Medicine, 2022)
Many viral infections can affect vision and the visual system. Vaccination to prevent diseases is commonplace today, acting by stimulating an immune response without developing the pathology. It involves the production of persisting antibodies against the pathogen and the activation of T cells. Certain diseases have already been eradicated by rigorous vaccination campaigns, while others are hoped to be eliminated soon. Vaccines currently available on the market are largely safe, even if they can rarely cause some adverse effects, such as ocular complications. Analyzing existing literature, we aimed to compare the pathological effects on the eye due to the most common viral infections [in particular varicella zoster virus (VZV), measles virus, influenza viruses, hepatitis B virus, and SARS-CoV-2] with the possible ocular adverse effects of their relative vaccines, in order to establish a risk-benefit relationship from an ophthalmological point of view.